Energy scenarios: the value and limits of scenario analysis. Issue 4 (28th December 2016) - Paltsev, Sergey
Abstract : A need for low‐carbon world has added a new challenging dimension for the long‐term energy scenarios development. In addition to the traditional factors like technological progress, demographic, economic, political, and institutional considerations, there is another aspect of the modern energy forecasts related to the coverage, timing, and stringency of policies to mitigate the greenhouse gas emissions and air pollutants. Modern tools for the energy scenario development provide a good basis for the estimates of the required changes in the energy system to achieve certain climate and environmental targets. While the current scenarios show that a move to a low‐carbon energy future requires a drastic change in energy investment and the resulting mix in energy technologies, the exact technology mix, paths to the needed mix, price, and cost projections should be treated with a great degree of caution. The scenarios do not provide exact predictions, but they can be used as a qualitative analysis of decision‐making risks associated with different pathways. If history is any guide, energy scenarios overestimate the extent to which the future will look like the recent past. As future costs and the resulting technology mixes are uncertain, a wise government policy is to target emissions reductions from any source, rather than focus on boosting certain kinds of low‐carbon energy. WIREs Energy Environ 2017, 6:e242. doi: 10.1002/wene.242 This article is categorized under: Energy and Climate > Economics and Policy Energy and Climate > Systems and Infrastructure Energy Policy and Planning > Economics and Policy Abstract : Historic oil prices for 2010–2014 and projected oil prices for 2015–2040. Data source: IEA, 6, 70 EIA. 72